Caracterização funcional de isolados de um concentrado protéico de soja produzidos no Brasil: Solubilidade e capacidade de absorção de água - Gomes, José Carlos; Fontes Araújo, Miriam; Alves Moreira, Maurílio; Teixeira Coelho, Dilson (Revista Ceres, 2025)
Five soybean protein isolates (Proteimax 90-SH, Proteimax 90-HG, Proteimax 90-NB, Proteimax 90-LV, and Proteimax 90-LG) and one soybean protein concentrate (Proteimax 70), produced in Brazil, were characterized in terms of solubility and water absorption capacity.